Kinetics of low‐temperature Fischer‐Tropsch synthesis on cobalt catalysts: Are both slurry autoclave and tubular packed‐bed reactors adequate to collect relevant data at lab‐scale?. (24th February 2016) - Visconti, Carlo Giorgio; Lietti, Luca; Tronconi, Enrico; Rossini, Stefano
Abstract: To verify the equivalence of kinetic data obtained in lab‐scale packed‐bed and slurry reactors for low‐temperature Fischer‐Tropsch synthesis over cobalt‐based catalysts, the same Co/γ‐Al2 O3 catalyst was tested in both reactors, studying the effects of the process conditions (temperature, pressure, syngas composition, gas space velocity) on CO conversion rate and on product distribution. Then, both a lumped CO conversion rate equation and detailed kinetics (i.e. describing the rates of reactants conversion and product formation) were developed based on the data collected in the packed‐bed tubular reactor. The two models were finally used to simulate the performance of the slurry autoclave. By describing the slurry autoclave as a continuous stirred tank reactor and the packed‐bed as plug‐flow reactor, the kinetic information collected with the two reactors is fully equivalent and can be used indiscriminately to describe the rates of reactant consumption and product formation.